Pengaruh Kemudahan Penggunaan dan Keamanan Terhadap Minat Menggunakan Gojek dengan Tingkat Kepercayaan Sebagai Variabel Moderasi - Apriliza, Yafika; Siregar, Dwi Faradiba; Putra, Ramadhan Diansyah; Gultom, Parapat (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
The purpose of this study was to analyze the effect of ease of use and security on the interest in using Gojek with the level of trust as a moderating variable in students of the Faculty of Economics and Business, Islamic University of North Sumatra. Data collection was carried out using a questionnaire and obtained 122 respondents. The analysis method used was Partial Least Square (PLS) with SmartPLS 3.0 software. The results showed that ease of use and security of Gojek had a significant positive effect on interest. However, the level of trust did not moderate the relationship between ease of use and security when using Gojek. The implication of this study is that PT Gojek Indonesia should continue to improve the usability and security of the application, in addition, researchers should also consider other factors that can affect users' desire to use Gojek. Keywords: Ease of Use, Security, Level of Trust, Interest Using